The Vision of Internationalization at Pondok Modern Darussalam Gontor: A Transnational Theory Perspective - Mubarok, Ahmad Zakky; Surwandono , Surwandono; Khakim, Usmanul (At-Ta'dib, 2025)
Purpose - Pondok Modern Darussalam Gontor (PMDG) is one of Indonesia’s most influential Islamic educational institutions, with alumni actively engaged at both national and international levels. This study explores the vision of internationalization at PMDG through the lens of transnational theory. Specifically, it applies both classical (high-politics) and contemporary (low-politics) models of transnationalism to analyze Gontor’s global orientation. Methods - Employing a qualitative content analysis based on literature and official documents, this study identifies key teachings of the kyai (religious leaders) that articulate international ideals. Findings – The findings reveal that PMDG adopts a new-style transnational approach, where education, ethical values, and cultural ideas become the core instruments of global engagement. These ideals are diffused internally through kyai-student interactions and mobilized externally by alumni across various countries and sectors. The study also finds that Gontor’s educational model is influenced by a synthesis of four international institutions: Al-Azhar, Syanggit, Santiniketan, and Aligarh. These form the epistemological foundation for its vision of Islamic global citizenship. Research Implications/ Limitations - include the need for further studies on Islamic educational institutions as soft power agents in international relations. the study lie in its reliance on textual sources, which may not fully capture the lived experiences of santri and alumni. Originality/value of this research lies in its application of transnational theory to analyze a pesantren’s educational vision, a subject rarely explored in prior scholarship.